An international consensus definition for contextual factors: findings from a nominal group technique - Cook, Chad E.; Bailliard, Antoine; Bent, Jennifer A.; Bialosky, Joel E.; Carlino, Elisa; Colloca, Luana; Esteves, Jorge E.; Newell, Dave; Palese, Alvisa; Reed, William R.; Vilardaga, Jennifer Plumb; Rossettini, Giacomo (Frontiers in Psychology, 2023)
Emerging literature suggests contextual factors are important components of therapeutic encounters and may substantially influence clinical outcomes of a treatment intervention. At present, a single consensus definition of contextual factors, which is universal across all health-related conditions is lacking. The objective of this study was to create a consensus definition of contextual factors to better refine this concept for clinicians and researchers. Our consensus definition of contextual factors seeks to improve the understanding and communication between clinicians and researchers. These are especially important in recognizing their potential role in moderating/mediating clinical outcomes.